The Influence of Complete Learning Facilities on Mathematics Learning Outcomes of Class V MI Nurul Ulum Madiun Students - Febri Hidayana, Avita (Jurnal Paradigma, 2021)
earning facilities are equipment that children need in learning, besides learning facilities are supporting children's learning success. In the field it was found that some students obtained learning outcomes that had not yet reached the minimum completeness criteria (KKM). This may be due to the above factors. Therefore, the researcher wanted to know the effect of the completeness of learning facilities on the Mathematics learning outcomes of Class V Students at MI Nurul Ulum Sidorejo Madiun. In this study, researchers used quantitative methods. The purpose of this study was to determine whether there is an effect of the completeness of learning facilities on student mathematics learning outcomes at MI Nurul Ulum Sidorejo Madiun. The data collection techniques used questionnaires and documentation. The population of this research is the fifth grade students of MI Nurul Ulum Sidorejo Kebonsari Madiun totaling 20 students. For data analysis techniques using Simple Linear Regression using SPSS 16.0 program. Based on the calculation at the 5% significance level, it shows that there is an effect of the completeness of learning facilities on students' mathematics learning outcomes of 41.4% or sufficiently influential while the rest is influenced by other variables.